Attention to olfaction. A psychophysical investigation. - Spence, C; McGlone, F; Kettenmann, B; Kobal, G (2001)
Olfaction is unique among the senses in that signals from the peripheral sensory receptors bypass the thalamus on their way to the cortex. The fact that olfactory stimuli are not gated by the thalamus has led some researchers to suggest that people may be unable to selectively direct their attention toward the olfactory modality. We examined this issue in an experiment where participants made speeded intensity (strong vs weak)-discrimination responses to an unpredictable sequence of olfactory and visual stimuli. Attention was directed to either olfaction or to vision by means of an informative cue that predicted the likely modality for the upcoming target on the majority of trials. Participants responded more rapidly when the target was presented in the expected rather than the unexpected modality, showing that people can selectively attend to olfaction.